Analisis Permasalahan Pembelajaran Teks Akademik dan Non Akademik di SMP Negeri 1 Patumbak Kecamatan Patumpak Kabupaten Deli Serdang - Suriyani, Dita; Syahputra, Fachri; Aulia, Lendy Annisa; Simanjuntak, Roriana (Universitas Muhammadiyah Enrekang, 2024)
Analysis of the Problems of Learning Academic and Non-Academic Texts in Schools was carried out with the aim of identifying problems related to academic and non-academic texts in schools. This research has benefits including helping to understand more deeply about Academic and Non-Academic Texts, Increasing knowledge about Indonesian Language Learning. , Makes it easier to get information about the various characteristics of Academic and Non-academic Texts, Helps prospective educators understand the differences between Academic and Non-academic Texts. The research was conducted at SMP N 1 Patumbak, Jl. Struggle III Hamlet 4, Sigara Gara, Kec. Patumbak, Deli Serdang Regency, North Sumatra